Lipofilling technique with Bichat ball material: a case report - Carneiro de Resende, Tatiana; Tereza Scardua, Maria; Vieira Camargo, Ricardo; Carlos Tolentino Barbosa, Joao; Peruzzo Rovaris, Denize; Cuzzuol Alvez, Karina; Pereira Alves, Lucas; de Souza Castro Filice, Letícia; de Azevedo, Fábio (Seven Editora, 2023)
Bichectomy constitutes the resection of the "Bola de Bichat", which, in addition to minimizing chronic trauma to the jugal mucosa resulting from chewing, considerably improves facial harmony, making the middle third of the face more contoured and symmetrical. The objective of the present study is to report the case of a patient with a verified and confirmed need to remove a Bichat ball for better occlusal functionality and conformity of facial harmonization with fat grafting of material from the bichectomy in the malar regions and angle of the mandible. The most interesting description in this unprecedented case report is the form of grafting and the type of material used, which has not yet been described in the literature. The volume of the fat graft stabilized around the 1st postoperative month. The authors valued the uniformity of the aesthetic unit. The present study demonstrates the effectiveness of bichectomy when there is a good indication and confirms the high aesthetic efficiency of autologous fat grafting with the Bichat ball in the mandibular and malar angle region, both in terms of distribution and volume maintenance, with no complication rate, in this reported case. DOI: https://doi.org/10.56238/tfisdwv1-157